Perivascular Brightness of Coronary Arteries in Kawasaki Disease - Yu, Jeong Jin; Jang, Wan-Sook; Ko, Hong Ki; Han, Myung-Ki; Kim, Young-Hwue; Ko, Jae-Kon; Park, In-Sook (The Journal of pediatrics, 2011)
Because perivascular echo brightness (PEB) of coronary arteries has been proposed as a criterion for diagnosis of incomplete Kawasaki disease, we assessed the clinical importance of PEB during the acute phase of disease. We enrolled 58 patients with Kawasaki disease who underwent two-dimensional strain analysis of images of pericoronary tissue taken during the acute and the convalescent phases. Echogenicity of pericoronary tissue and of the blood pool was determined by speckle tracking in the respective areas of imaging as the averages of integrated backscatter over a single cardiac cycle. PEB was defined as echogenicity of pericoronary tissue minus blood pool. PEB did not differ in the acute phase in patients and control subjects ( P = .10) and between phases of disease ( P = .25). In comparison between patient groups, the presence of pericardial effusion was higher in patients with higher PEB during the acute phase (n = 30) than in the remaining patients (33% versus 4%, P < .01). PEB did not differ between patients and control subjects and is only associated with the presence of pericardial effusion during the acute phase of Kawasaki disease. Our data do not confirm the reliability of PEB as a useful diagnostic sign of incomplete Kawasaki disease.